1990
DOI: 10.1901/jaba.1990.23-119
|View full text |Cite
|
Sign up to set email alerts
|

Extended Reductions in Stereotypic Behavior of Students With Autism Through a Self‐management Treatment Package

Abstract: The literature suggests that self-management treatment packages have two potential strengths for the reduction or elimination of stereotypic behavior: (a) Self-management may be used for extended periods of time in the absence of a treatment provider, and (b) self-management techniques are easily adapated and used in a wide variety of natural settings. We assessed whether students with severe autistic disabilities could learn to use a self-management treatment package to reduce their stereotypic behavior withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
14

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 13 publications
3
69
1
14
Order By: Relevance
“…DISCUSSION Overall, the results of this study showed that the lack ofsocial responsivity that is so characteristic in autism can be successfully treated with selfmanagement procedures, requiring minimal presence of a treatment provider in the children's natural environments. Other studies corroborate these findings, suggesting that self-management may be an especially promising intervention for children with autism when minimal therapist presence is desired (e.g., Johnson, 1991;R. Koegel & Koegel, 1990;Stahmer & Schreibman, 1992).…”
Section: Accuracy Of Self-recordingmentioning
confidence: 85%
See 1 more Smart Citation
“…DISCUSSION Overall, the results of this study showed that the lack ofsocial responsivity that is so characteristic in autism can be successfully treated with selfmanagement procedures, requiring minimal presence of a treatment provider in the children's natural environments. Other studies corroborate these findings, suggesting that self-management may be an especially promising intervention for children with autism when minimal therapist presence is desired (e.g., Johnson, 1991;R. Koegel & Koegel, 1990;Stahmer & Schreibman, 1992).…”
Section: Accuracy Of Self-recordingmentioning
confidence: 85%
“…Self-management (R. Koegel & Koegel, 1990) is one treatment technique that has been found effective with speech sounds of children (L. Koegel, Koegel, & Ingham, 1986), academic skills with learning-disabled children (Harris, 1986), and in the treatment of children with developmental disabilities. Teadcing self-management techniques allows the child to manage his or her own behavior in the absence of a treatment provider for potentially long periods (cf.…”
mentioning
confidence: 99%
“…For example, Christie, Hiss, and Lozanoff (1984) used self-monitoring techniques to increase attention and decrease inappropriate classroom behaviors of 3 elementary school children with behavior problems. Rhode, Morgan, and Young (1983) used self-monitoring to facilitate generalization, as did Koegel and Koegel (1990) and Warrenfeltz et al (1981). Thus, self-monitoring strategies can be helpful in improving behavior, in reducing the salience of external management, and in transferring effective behavioral control to different environments.…”
mentioning
confidence: 99%
“…There is a significant body of research concerning what was named as incidental teaching and variations and the discussion about their effectiveness in producing generalization. The reader may refer to the literature about the theme for details on naturalistic procedures (Allen & Cowan, 2008;Dunlap & Koegel, 1980;Eikeseth, Smith, Jahr, & Eldevik, 2002;Halle, Baer, & Spradlin, 1981;Halle, Marshall, & Spradlin, 1979;Harris & Handleman, 2000;Hart & Risley, 1968;Koegel, Bimbela & Schreibman, 1996;Koegel, Dyer, & Bell, 1987;Koegel & Egel, 1979;Koegel et al, 2012;Koegel & Koegel, 1990;Koegel, Koegel, Green-Hopkins, & Barnes, 2010;Koegel, O'Dell & Dunlap, 1988;Koegel, O'Dell & Koegel, 1987;Koegel, Werner, Vismara, & Koegel, 2005;Koegel & Williams, 1980;Krantz & McClannahan, 1993, 1998Ledbetter-Cho et al, 2015;Lovaas, 1987;Lovaas, 2003;McGee, Krantz & McClannahan, 1985;Miranda-Linne & Melin, 1992;Mobayeb et al, 2000;Pierce & Schreibman, 1995, 1997Rogers-Warren & Warren, 1980;Schreibman, Kaneko & Koegel, 1991;Sheinkopf & Siegel, 1998;Valenti, Cerbo, Masedu, De Caris, & Sorge, 2010;Warren, McQuarter, & Rogers-Warren, 1984;Williams, Koegel, & Egel, 1981).…”
Section: C De Matos P G S De Matos Psychologymentioning
confidence: 99%